Predictive Indicators for Necrotizing Enterocolitis With the Presence of Portal Venous Gas and Outcomes of Surgical Interventions - Lin, Xin; Zeng, Hui-Ping; Fang, Yi-Fan; Lin, Ying-Ying; Yang, Chang-Yi (Frontiers in Pediatrics, 2021)
Objectives: Portal venous gas (PVG) was an important clinical sign in the stage II or III of necrotizing enterocolitis (NEC) in preterm neonates. Not a proper predictive indicator was found to predict the diseases (NEC with the presence of PVG) up to now. There is a need to put forward predictive indicators and compare the predictive effects among them. Methods: We conducted a retrospective study of preterm neonates with NEC-PVG (n=61) or NEC-non PVG (n=62) from 2014 to 2021. Predictive indicators were put forward and determined by receiver operating characteristic curve analysis. An analysis of the surgical interventions and the outcomes of them was performed. Results: The incidence rate of NEC among preterm neonates was 4.99%; surgical and conservative interventions accounting for 20.47% and 75.07%, and the mortality rate was 0.03%. The composition ratio of shock in the NEC-PVG group increased 13.2% (P=0.029). C-reactive protein, fibrinogen degradation product, and blood glucose had better predictive effects in the predictive indicators (P<0.05). Intestinal necrosis, and subependymal hemorrhage in the outcomes of surgical interventions had a strong relationship with the presence of PVG in NEC II/III (P<0.05). Conclusion: Early and reasonable use of antibiotics, improvement of coagulation function, rectification of acidosis, and decreased blood glucose could cut down the occurrence of the disease (NEC with the presence of PVG). Except for subependymal hemorrhage and intestinal necrosis, NEC with the presence of PVG did not increase the occurrence of other outcomes after surgery.